Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fvets.2020.572142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics and Multi-Component Feed Additives on Microbiota, Gut Barrier and Immune Responses in Broiler Chickens During Subclinical Necrotic Enteritis

Abstract: The withdrawal of antibiotic growth promoters from poultry feed has increased the risk of necrotic enteritis (NE) outbreaks. This study examined the effects of a probiotic (PROB) or probiotic/prebiotic/essential oil supplement (PPEO) during a subclinical NE challenge. On day (d) of hatch, 960 male broilers were randomized to four groups (8 pens/treatment, 30 birds/pen) including (1) negative control (NC): corn-soybean meal diet; (2) positive control (PC): NC + 20 g Virginiamycin/ton diet; (3) NC + 227 g PROB/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Meanwhile, they mainly modulated the functions of Th1, Th17, and Treg cells. However, Emami et al ( 25 ) reported that Bacillus licheniformis alone or combined with prebiotic and essential oil downregulated the IFN-γ, IL-10, and IL-17 mRNA abundance in the jejunum of broilers with subclinical NE, indicating a inhibition of Th2, Th17, and Treg cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, they mainly modulated the functions of Th1, Th17, and Treg cells. However, Emami et al ( 25 ) reported that Bacillus licheniformis alone or combined with prebiotic and essential oil downregulated the IFN-γ, IL-10, and IL-17 mRNA abundance in the jejunum of broilers with subclinical NE, indicating a inhibition of Th2, Th17, and Treg cell function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that there was a positive correlation between the relative abundance of Escherichia-Shigella with NE occurrence in broilers ( 45 ). Numerous studies evidenced that C. perfringens challenge increased the Escherichia-Shigella abundance in the ileum, and probiotic supplementation significantly or numerically decreased it ( 13 , 25 ). However, in the present study, C. perfringens challenge decreased Escherichia-Shigella in the cecum on day 28, which was increased by B. coagulans .…”
Section: Discussionmentioning
confidence: 99%
“…To simulate field conditions, a unique, naturally occurring model developed by our laboratory was applied to induce subclinical NE ( Calik et al., 2019 ; Emami et al., 2019 , 2020 ) using a concentrated dose of a commercial coccidiosis vaccine. Briefly, this model consists of spraying a high dose (10 X) of commercial coccidiosis vaccine 24 h after bird placement, which in conjunction with the presence of C .…”
Section: Methodsmentioning
confidence: 99%
“…The 16S sequencing data were analyzed as previously described ( Emami et al., 2020 ). Briefly, data were analyzed using quantitative insight into microbial ecology ( QIIME ) software package 2 ( Bolyen et al., 2019 ) and samples for day 8 and day 28 were rarefied to 10,891 and 36,075 sequences, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A ban on the use of antibiotic growth promoters (AGPs) has energized scientific research to identify reliable and effective alternatives. Probiotics, prebiotics, synbiotics, organic acids, antimicrobial peptides, and phytogenics are among the various groups of alternatives to in-feed antibiotics that have gained popularity in animal production research [ 1 , 2 , 3 , 4 ]. Phytogenics, also called phytobiotics or botanicals, are a growing class of in-feed products derived from plants and plant products such as herbs, spices, essential oils, and blends of these products.…”
Section: Introductionmentioning
confidence: 99%